Maxillofacial Prosthetic Materials: A Literature Review - Mahajan, Harsh; Gupta, Kshitij (Journal of Orofacial Research, 2012)
Rehabilitation of patients with disabilities of head and neck region, due to either congenital or acquired defects is a challenging task. These defects range from minor cosmeticdiscrepancies to major functional limitation. The prosthodontics management of these patients should aim at not only restoring the functional and esthetic handicap, but also ensurepsychological well being. For facial rehabilitation assessment of materials used in maxillofacial prosthesis is necessary. Till date we have come a cross various materials which exhibitsome excellent properties but also have many deficiencies. This article will review various materials used in maxillofacial prosthesis.